Phytosociological description of Ostrya carpinifolia and Fraxinus ornus communities in the Julian Alps and in the northern part of the Dinaric Alps (NW and W Slovenia, NE Italy) - Dakskobler, Igor (Hacquetia, 2015)
Based on comparisons between similar communities in northeastern Italy, southern Austria, central and southeastern Slovenia, and western Croatia, we classified black hornbeam and flowering ash phytocoenoses on steep rocky sites in the beech forest belt in northwestern and western Slovenia into the association Fraxinio orni-Ostryetum Aichinger 1933 and described its new subassociation -phyteumatetosum columnae in the foothills of the Julian Alps and in the northern part of the Dinaric Alps. Black hornbeam and flowering ash stands on steep shady slopes with a higher proportion of diagnostic species of beech and spruce forests are classified into the new association Rhododendro hirsuti-Ostryetum Franz ex Dakskobler, ass. nov. hoc loco, new subassociation -mercurialietosum perennis and the provisional variant var. Hemerocallis lilioasphodelus whose stands are floristically rather similar to the stands of the association Hemerocallido-ostryetum.